NEW FORMS OF INTEGRATION OF BUSINESS: METHODOLOGY QUESTIONS - Valentina V. Gromyko (Вестник Российского экономического университета имени Г. В. Плеханова)
In article on the basis of dialectic approach the essence of the concept 'integration' is defined and five main theoretical treatments of integration are given: dialectic antipode of differentiation; merge and absorption; strategic alliance and control; basis of formation of multinational corporation and MNK; interstate economic cooperation and association. By the author it is shown that integration has to be considered in dialectic unity with differentiation. It is proved that forms of integration of business answer its purpose, strategy and a concrete situation. Value of coordination as key moment of realization of integration processes reveals, dialectic communication of mechanisms of marketability and regularity for realization of multilevel system of economic interests and the purposes is presented. Some features of forms of integration of business in Russia are analysed.